Operando neutron imaging study of a commercial Li-ion battery at variable charge-discharge current densities. (20th September 2022) - Nazer, Nazia S.; Strobl, Markus; Kaestner, Anders; Vie, Preben J.S.; Yartys, Volodymyr A.
Highlights: Commercial Li ion cylindrical battery has been studied operando by neutron imaging. It has been charged and discharged at current densities 1C and 2C. Circulation of electrolyte was observed during charge-discharge. Radiographs exhibited inhomogeneous distribution of lithium throughout the battery. Ex-situ neutron tomography visualised the battery architecture. Abstract: We report an operando neutron imaging study of a commercial ICR 10440 Li ion battery during charge and discharge. The cylindrical battery with a spiral configuration is composed of a multiphase layered oxide cathode and graphite anode. In spite of a two-dimensional nature of the projection data of this time-resolved study, structural and functional details of the neutron radiography study were successfully uncovered and visualized. The spatially resolved measurements with a resolution of 40 µm enabled to observe Li redistribution between the electrodes as well as a circulation of the electrolyte between the central column and the electrode layers at different states of charge (SoC) and at different current rates. Furthermore, ex-situ tomographic studies of the battery revealed the fine details of the structural inhomogeneity within the cell.